A novel SCN1A mutation identified in a Chinese family with familial hemiplegic migraine: A case report. (November 2017) - Zhang, Yang; Chen, Ning; Zhou, Muke; Guo, Jian; Guo, Jiang; He, Li
Background: Familial hemiplegic migraine (FHM) is a rare type of migraine with aura that is characterized by transient hemiparesis. Mutations in three genes (CACNA1A, ATP1A2, and SCN1A) have been found to cause FHM. Among these, nine SCN1A gene mutations were reported to cause familial hemiplegic migraine type 3 (FHM3). However, none of them was reported in China. Method: The clinical manifestations of a Chinese FHM family were recorded and all coding exons and flanking intronic regions of the CACNA1A, ATP1A2, and SCN1A genes were tested for mutations. Results: All FHM patients in the investigated family have typical hemiplegic migraine attacks characteristic of FHM. We identified a novel mutation (p.Leu1670Trp) of the SCN1A gene. The affected amino acid is highly conserved across different species and therefore likely plays an important role in SCN1A gene function. Conclusion: The identification of a novel mutation in the SCN1A gene in the Chinese population may further aid in the understanding of FHM genetics.